INTERNALIZATION OF PAI VALUES IN FORMING STUDENTS' RELIGIOUS CHARACTER IN PRIMARY SCHOOL - Kamilah, Fitrotul; Aisyah, Nur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The process of unifying values within a person through appreciating, understanding, instilling and cultivating values, attitudes, teachings or beliefs from the surrounding environment which then unite and become knowledge that influences a person's life and is then reflected in daily behavior which is carried out intensively and continuously with the aim of to always maintain Islamic teachings, especially for students and graduates. The aim of this research article is to present information related to the internalization of PAI values in forming religious character in students at SD Negeri 1 Tiris Probolinggo. This research uses a qualitative, descriptive approach that focuses on PAI learning in efforts and efforts to shape the religious character of students at SD Negeri 1 Tiris Probolinggo, data collection techniques using interviews, observation and documentation which are analyzed descriptively. Meanwhile, the data analysis used is data reduction, data presentation, and drawing conclusions